Development of Pictorial-based Two-Tier Multiple Choice Misconception Diagnostic Test on Buffer Solutions - Setia Rahmawan; Harry Firman; Wiwi Siswaningsih; Dea Santika Rahayu (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aims to develop a Pictorial-based Two-Tier Multiple Choice Misconception Diagnostic Test on Buffer Solutions. This research uses the Development and Validation method. The development steps in this method consist of test development (design); validity and reliability test; development of determination key; use of tests, and analysis of results. Based on the content validity test using the Content Validity Ratio (CVR) method, there are 24 items meet the content validity criteria. Based on the reliability test obtained Cronbach's Alpha value of 0.827 which indicates that the developed test is included in the acceptable category. It can identify high school students' misconceptions about the buffer solutions because the presence of pictures can help students understand the problems about the buffer solutions, and can provide an overview of their mental representations so that misconceptions are revealed more deeply.